Enhancing biodiversity through sowing and reduced management of grasslands on dikes and floodplains - Andrea R. Schneider; Dominik Buchner; Rike Bayer; Willem Kaijser; Svenja Karnatz; Daniel Hering (Basic and Applied Ecology, 2025)
Grassland on dikes and in floodplains offers great potential to enhance biodiversity, particularly in urban areas. This study investigates the effects of changing the management from intensive mowing to reduced management on community composition, species richness, Shannon diversity, and functional traits for vegetation, general arthropods, and epigean carabids. Along the rivers Emscher and Lippe, 16 sites were studied. Reduced management’ was characterized by sowing native species and mowing twice annually with cutting removal, while intensive management’ included frequent mowing and mulching. Sites were investigated where reduced management was established recently or several years ago. Reduced management increased species richness and altered community composition across all groups compared to intensive management. Plant species richness increased by 5.7, general arthropods by 4.8, and epigean carabids by 0.7. No significant differences were observed between short- and long-term implementation. Ruderal and stress-tolerant plant species dominated vegetation in intensively managed sites, while reduced sites supported more specialized feeding types across insect species and floodplain-specific carabids. Larger, univoltine arthropods were more common in reduced sites. Sowing native grassland species and changing the management from intensive to reduced mowing can increase biodiversity and favor specialist species. This effect is achieved within a short time after implementation and remains effective in the long term. Conversion from intensive to reduced management is, therefore, an important strategy for increasing biodiversity and resilience of grasslands in urban floodplains.